Analisis Yuridis Perlindungan Hukum Pekerja Migran Indonesia Menurut Undang-Undang Nomor 18 Tahun 2017 Tentang Perlindungan PMI - Mulyanto Mulyanto; Miftahul Huda (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Indonesian Migrant Workers (PMI) play a crucial role in the nation's economy, as shown by their participation in overseas employment and the remittances they send back. Nevertheless, PMI frequently encounter challenges such as abuse, exploitation, breaches of contracts, and limited access to legal protections. The comprehensive legal structure designed to ensure their inclusive safety before, during, and after their employment is laid out in Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers. This research aims to analyze the actual practice of legal protections available to PMI, in light of statutory requirements, and to highlight any obstacles encountered in its application. A normative legal research method is used in this study, employing both legislative and theoretical frameworks, and it is informed by relevant academic literature, laws, and judicial rulings. The findings reveal that while Law No. 18 of 2017 outlines thorough protection protocols, its real-world execution faces hurdles such as insufficient oversight, poor cooperation among agencies, and a general lack of legal knowledge among PMI. Consequently, it is essential to enhance institutions, elevate the quality of protective services, and maximize the effectiveness of Indonesian representatives abroad. This study aims to contribute to the development of more equitable and efficient regulations for the safeguarding of migrant workers.